(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article discusses samples of a work of art in Russian and Uzbek literature. Literature lessons provide an opportunity to compare and contrast the literature of other nations and peoples, enrich students’ knowledge, expand their understanding of fiction. Translation is very important for fulfilling the sacred task of introducing our people to the great achievements of world science, technology, culture and the development of social thought, educating them in the spirit of friendship between peoples. The most important thing that is required of the translator is not the general content and idea of the work, but the specific language and style of the author, his form of artistic observation; it is required to fully reflect not the external and superficial body and grace of the book, but its main character: inner warmth and artistic features. The article analyzes samples of Russian literature selected for classes in the Uzbek language, which were performed by experienced translators Oybek, Abdulla Kakhhor, Erkin Vakhidov and others, and the fact that the translated language of the works is true to the original and created in its pure form attracts the attention of students and teachers.